2020
DOI: 10.1158/1535-7163.mct-20-0182
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lysosomal Function Mitigates Protective Mitophagy and Augments Ceramide Nanoliposome–Induced Cell Death in Head and Neck Squamous Cell Carcinoma

Abstract: Therapies for head and neck squamous cell carcinoma (HNSCC) are, at best, moderately effective, underscoring the need for new therapeutic strategies. Ceramide treatment leads to cell death as a consequence of mitochondrial damage by generating oxidative stress and causing mitochondrial permeability. However, HNSCC cells are able to resist cell death through mitochondria repair via mitophagy. Through the use of the C6-ceramide nanoliposome (CNL) to deliver therapeutic levels of bioactive ceramide, we demonstrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Preclinical assays with cell lines and xenografts show that CNLs potentiate the effect of chemotherapy ( 114 116 , 120 ); reduce tumor proliferation mediated by apoptosis (increased cleavage of PARP and caspases) ( 110 112 , 114 , 116 119 , 121 , 123 ), autophagy (increased LC3-II and Atg5 levels) ( 117 , 122 ), necrosis ( 106 ), necroptosis ( 109 ), anoikis ( 108 ), mitophagy (mitochondrial membrane permeabilization) ( 116 , 119 , 121 123 ), and cell cycle arrest (increased p53 expression) ( 116 , 119 ); increase ROS levels ( 110 ); inhibit lysosomal function ( 116 , 122 ); inhibit integrin affinity ( 105 , 107 ); and target CD44 receptor ( 108 ), survivin ( 111 ), PI3K ( 107 , 114 ), MAPK ( 105 , 114 ), mammalian target of rapamycin (mTOR) ( 112 , 121 ), Akt and Erk1/2 ( 110 , 115 ) signaling ( Figure 3 ). For example, Shaw et al.…”
Section: Ceramide Nanoliposomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical assays with cell lines and xenografts show that CNLs potentiate the effect of chemotherapy ( 114 116 , 120 ); reduce tumor proliferation mediated by apoptosis (increased cleavage of PARP and caspases) ( 110 112 , 114 , 116 119 , 121 , 123 ), autophagy (increased LC3-II and Atg5 levels) ( 117 , 122 ), necrosis ( 106 ), necroptosis ( 109 ), anoikis ( 108 ), mitophagy (mitochondrial membrane permeabilization) ( 116 , 119 , 121 123 ), and cell cycle arrest (increased p53 expression) ( 116 , 119 ); increase ROS levels ( 110 ); inhibit lysosomal function ( 116 , 122 ); inhibit integrin affinity ( 105 , 107 ); and target CD44 receptor ( 108 ), survivin ( 111 ), PI3K ( 107 , 114 ), MAPK ( 105 , 114 ), mammalian target of rapamycin (mTOR) ( 112 , 121 ), Akt and Erk1/2 ( 110 , 115 ) signaling ( Figure 3 ). For example, Shaw et al.…”
Section: Ceramide Nanoliposomesmentioning
confidence: 99%
“…For example, Shaw et al. indicated that the combination of C6-CNLs with chloroquine (an inhibitor of lysosomal function and therefore an autophagy inhibitor) significantly increases apoptosis in response to ceramide by avoiding the repair of mitochondrial damage ( 122 ).…”
Section: Ceramide Nanoliposomesmentioning
confidence: 99%
“…As mentioned in Section 3.2, cancer may upregulate basal mitophagy in a protective manner to reduce reactive oxygen species and restore depolarized mitochondria during chemotherapeutic treatment. Disruption of cancer-induced protective mitophagy through the use of lysosomal inhibitors was found to sensitize drug-resistant HNSCC cells to C6-ceramide nanoliposome delivery of therapeutic ceramide [174]. Conversely, knocking down neutral ceramidase in mouse embryonic fibroblasts stimulated protective autophagy and ceramide generation to protect against drug-induced necroptosis [175].…”
Section: Cancer Therapy and Drug Resistancementioning
confidence: 99%
“…Indeed, many vaccines benefit from lipid-based delivery. Of particular note are the recently authorized COVID-19 vaccines, which utilize lipid nanoparticles containing antigenencoding RNA [18,19] . Our team has been successful in the use of nanotechnologies, including nanoliposomes, for a host of different therapies [20][21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…Of particular note are the recently authorized COVID-19 vaccines, which utilize lipid nanoparticles containing antigen-encoding RNA [ 18 , 19 ] . Our team has been successful in the use of nanotechnologies, including nanoliposomes, for a host of different therapies [ 20 - 25 ] . Nanoliposomes have the capability of altering the pharmacokinetic properties of antigens and immunomodulators/adjuvants, with a marked reduction in off-target toxicity, protection of the therapeutic from degradation, along with more specific targeting to antigen-presenting cells [ 26 ] .…”
Section: Introductionmentioning
confidence: 99%